Acrylic acid catalyst based on spinel structure carrier as well as preparation method and application of acrylic acid catalyst

By using a magnesium aluminum spinel structural support and impregnation method in the acrylic catalyst, the use efficiency of active metals and the support strength of the catalyst are improved, and the problems of low utilization efficiency of active metals and high wear rate of catalyst strength in the prior art are solved.

CN119680563APending Publication Date: 2025-03-25SHANGHAI REZEL KEHUA ENG DESIGN CO LTD

Patent Information

Application Number
CN202411873187.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing acrylic catalysts have low utilization efficiency of active metals during application, and the strength and wear rate of the catalyst are high.

Method used

Using an acrylic catalyst with a spinel structure support, the use efficiency of active metals and the support strength of the catalyst are improved by using a support with a magnesium aluminum spinel structure and an impregnation method.

Benefits of technology

The use efficiency of active metals and the support strength of the catalyst are improved, and the problems of low utilization efficiency of active metals and high catalyst strength wear rate in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680563A_ABST
    Figure CN119680563A_ABST
Patent Text Reader

Abstract

The invention relates to an acrylic acid catalyst based on a spinel structure carrier and a preparation method and application thereof, and relates to the technical field of acrylic acid catalysts, the preparation method comprises the following steps: mixing pseudo-boehmite, magnesium nitrate and activated carbon powder, then adding vaseline, and continuing mixing to obtain a first mixture; adding ammonium fluoride and water into the first mixture, and mixing to obtain a second mixture; carrying out extrusion molding and grain-sized dicing on the second mixture, and then carrying out first drying and first roasting to obtain an Al2O3 carrier with a magnesium aluminate spinel structure; and dipping the Al2O3 carrier in a solution containing a metal active component, and then carrying out second drying and second roasting to obtain the acrylic acid catalyst. By using the carrier with the magnesium aluminate spinel structure and adopting an impregnation method, not only is the use efficiency of active metal improved, but also the strength of the carrier of the catalyst is improved, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic acid catalysts, and in particular to an acrylic acid catalyst based on a spinel structure carrier and a preparation method and application thereof. Background Art

[0002] Acrylic acid is an organic raw material with a wide range of applications in chemical fiber, textile, leather, building materials and other fields. Currently, the industrial oxidation of propylene to produce acrylic acid uses Mo-V composite oxide catalysts. Crude acrylic acid is mainly used to produce water-soluble coatings and adhesives, and refined acrylic acid is mainly used to produce highly absorbent resin SAP.

[0003] So far, Chinese patents CN1070468C, CN1031488A, CN1146438A, CN100378058C, CN1031050C, CN1169619C, CN1583261A and CN1146439A have reported related inventions of catalysts for the production of acrylic acid from propylene, among which molybdenum-vanadium catalysts are the main ones. The catalysts in the above patents are prepared by coprecipitation method to prepare powder, followed by calcination, crushing and molding. The main components of the catalysts are composite compounds composed of molybdenum, vanadium, copper, tellurium, molybdenum, nickel, iron, silicon, aluminum, alkali metals and alkaline earth metals, and the components of the catalysts are relatively complex.

[0004] At present, the preparation method of acrylic acid catalyst is to prepare Mo-V based catalyst by coprecipitation method. However, the catalyst prepared by coprecipitation method has low utilization efficiency of active metals during application, and most of them are in an inactive state. At the same time, due to the mixed molding of raw materials, the strength and wear rate of the catalyst are also very high. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an acrylic acid catalyst based on a spinel structure carrier and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a method for preparing an acrylic acid catalyst based on a spinel structure carrier, the preparation method comprising the following steps:

[0007] Pseudo-boehmite, magnesium nitrate and activated carbon powder are mixed, and then vaseline is added and mixed continuously to obtain a first mixture;

[0008] adding ammonium fluoride and water to the first mixed material and mixing them to obtain a second mixed material;

[0009] The second mixed material is extruded and pelletized, and then first dried and first calcined to obtain an Al2O3 carrier having a magnesium aluminum spinel structure;

[0010] The Al2O3 carrier is impregnated in a solution containing metal active components, and then subjected to a second drying and a second calcination to obtain the acrylic acid catalyst.

[0011] Furthermore, the weight ratio of the pseudo-boehmite, the magnesium nitrate, the activated carbon powder, the vaseline, the ammonium fluoride and the water is (50-55):(0-5):(0-1):(0-1):(0-1):(20-35).

[0012] Furthermore, the working condition parameters of the first drying include: drying at a temperature of 95 to 110° C. for 10 to 14 hours; the working condition parameters of the first roasting include: roasting at a temperature of 950 to 1250° C. for 3 to 5 hours.

[0013] Furthermore, the physical and chemical property parameters of the Al2O3 carrier having a magnesium-aluminum spinel structure include: a specific surface area of ​​10 to 40 m 2 / g, strength 110~150N / cm.

[0014] Furthermore, the metal active component includes at least one of a molybdenum source, a vanadium source, a bismuth source, a copper source and a tungsten source; the molybdenum source includes ammonium heptamolybdate, the vanadium source includes ammonium metavanadate, the bismuth source includes bismuth nitrate, the copper source includes copper nitrate, and the tungsten source includes ammonium metatungstate.

[0015] Furthermore, the weight ratio of the Al2O3 carrier to the solution containing the metal active component is (0.1-1):(0.5-1.35).

[0016] Furthermore, the working condition parameters of the second drying include: drying at a temperature of 70 to 90° C. for 8 to 10 hours; the working condition parameters of the second calcining include: calcining at a temperature of 400 to 600° C. for 3 to 5 hours.

[0017] In a second aspect, the present invention provides an acrylic acid catalyst based on a spinel structure carrier, wherein the acrylic acid catalyst based on a spinel structure carrier is prepared by the preparation method of the acrylic acid catalyst based on a spinel structure carrier described in any one of the first aspects.

[0018] In a third aspect, the present invention provides use of the acrylic acid catalyst based on a spinel structure carrier as described in any one of the second aspects in the preparation of acrylic acid using acrolein as a raw material.

[0019] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0020] The embodiment of the present invention provides a method for preparing an acrylic acid catalyst based on a spinel structure carrier. The present invention uses a magnesium aluminum spinel structure carrier and adopts an impregnation method, which not only improves the use efficiency of the active metal, but also improves the strength of the catalyst carrier, thereby making up for the shortcomings of the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0023] Figure 1 A schematic flow chart of a method for preparing an acrylic acid catalyst based on a spinel structure carrier provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0026] In a first aspect, the present invention provides a method for preparing an acrylic acid catalyst based on a spinel structure carrier, such as Figure 1 As shown, the preparation method comprises the following steps:

[0027] Pseudo-boehmite, magnesium nitrate and activated carbon powder are mixed, and then vaseline is added and mixed continuously to obtain a first mixture;

[0028] adding ammonium fluoride and water to the first mixed material and mixing them to obtain a second mixed material;

[0029] The second mixed material is extruded and pelletized, and then first dried and first calcined to obtain an Al2O3 carrier having a magnesium aluminum spinel structure;

[0030] The Al2O3 carrier is impregnated in a solution containing metal active components, and then subjected to a second drying and a second calcination to obtain the acrylic acid catalyst.

[0031] The embodiment of the present invention provides a method for preparing an acrylic acid catalyst based on a spinel structure carrier. The present invention uses a magnesium aluminum spinel structure carrier and adopts an impregnation method, which not only improves the use efficiency of the active metal, but also improves the strength of the catalyst carrier, thereby making up for the shortcomings of the prior art.

[0032] In some specific embodiments, the weight ratio of the pseudo-boehmite, the magnesium nitrate, the activated carbon powder, the vaseline, the ammonium fluoride and the water is (50-80):(0-5):(0-1):(0-1):(0-1):(20-36).

[0033] In some specific embodiments, the working condition parameters of the first drying include: drying at a temperature of 95-110° C. for 10-14 hours; the working condition parameters of the first calcining include: calcining at a temperature of 950-1250° C. for 3-5 hours.

[0034] In some specific embodiments, the physical and chemical property parameters of the Al2O3 carrier having a magnesium aluminum spinel structure include:

[0035] Specific surface area 10~40m 2 / g, strength 110~150N / cm.

[0036] In some specific embodiments, the metal active component includes at least one of a molybdenum source, a vanadium source, a bismuth source, a copper source and a tungsten source; the molybdenum source includes ammonium heptamolybdate, the vanadium source includes ammonium metavanadate, the bismuth source includes bismuth nitrate, the copper source includes copper nitrate, and the tungsten source includes ammonium metatungstate.

[0037] In some specific embodiments, the weight ratio of the Al2O3 carrier to the solution containing the metal active component is (0.1-1):(0.5-1.35).

[0038] In some specific embodiments, the working condition parameters of the second drying include: drying at a temperature of 70-90° C. for 8-10 hours; the working condition parameters of the second calcining include: calcining at a temperature of 400-600° C. for 3-5 hours.

[0039] In a second aspect, the present invention provides an acrylic acid catalyst based on a spinel structure carrier, wherein the acrylic acid catalyst based on a spinel structure carrier is prepared by the preparation method of the acrylic acid catalyst based on a spinel structure carrier described in any one of the first aspects.

[0040] In a third aspect, the present invention provides use of the acrylic acid catalyst based on a spinel structure carrier as described in any one of the second aspects in the preparation of acrylic acid using acrolein as a raw material.

[0041] It should be noted that, the acrylic acid catalyst based on a spinel structure carrier provided in the embodiments of the present invention, and the various components involved in the preparation method and application thereof, unless otherwise specified or specified, can all be commercially available products; at the same time, the steps and parameters involved in the preparation method, unless otherwise specified or specified, can all be carried out according to existing processes or using existing equipment.

[0042] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0043] Example 1

[0044] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0045] Preparation of the carrier: Weigh 1000g of pseudo-boehmite, 100g of magnesium nitrate, and 20g of activated carbon powder and add them to a kneader for dry mixing for 30 minutes. Continue to add 10g of vaseline and continue mixing for 30 minutes, then add 25g of ammonium fluoride and 80g of water to make a solution and add it to the kneader to mix for 30 minutes, then add 80g of nitric acid and 600g of water to make a solution and continue kneading for 20 minutes. Then put it into the extruder to extrude five-hole strips, cut into pellets, and then dry at 100℃ for 12 hours. After calcining at 1050℃ for 4 hours, an Al2O3 carrier with a magnesium aluminum spinel structure is obtained, which is recorded as carrier 1. Specific surface area 35m 2 / g, strength 120N / cm, water pore volume 0.65g / cm 3 .

[0046] Preparation of catalyst:

[0047] Weigh 411.5 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. 24 ·4H2O), 40.15g ammonium metavanadate (NH4VO3), 50.11g ammonium metatungstate ((NH4)6H2W 12 O 40·nH2O), 4.35g of copper nitrate (Cu(NO3)2) was dissolved in 250g of deionized water to obtain a solution, and the excess water was evaporated. The solution was added to the impregnation bottle of the carrier, and after impregnation, the wet material was placed at 80°C for 8-10 hours and then calcined at 500°C for 4 hours to obtain catalyst 1.

[0048] Example 2

[0049] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0050] Preparation of carrier: same as in Example 1.

[0051] Preparation of catalyst:

[0052] Weigh 394 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. 24 ·4H2O), 40.15g ammonium metavanadate (NH4VO3), 83.29g bismuth nitrate (Bi(NO3)3), 50.11g ammonium metatungstate ((NH4)6H2W 12 O 40 ·nH2O), 4.35g of copper nitrate (Cu(NO3)2) was dissolved in 300g of deionized water to obtain an impregnation solution, the mass ratio of the carrier to the impregnation solution was 1:1.35, the solution was added to the impregnation bottle of the carrier, after impregnation evenly, the excess water was evaporated. The above wet material was placed at 80℃ and dried for 8-10 hours, and then calcined at 500℃ for 4 hours to obtain catalyst 2.

[0053] Example 3

[0054] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0055] Preparation of carrier: same as in Example 1.

[0056] Preparation of catalyst:

[0057] Weigh 419 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. Add 86.61 g of ammonium heptamolybdate ((NH4)6Mo7O 24 ·4H2O), 22.95 g ammonium metavanadate (NH4VO3), 47.60 g bismuth nitrate, 50.11 g ammonium metatungstate ((NH4)6H2W 12 O 40·nH2O), 4.35 g of copper nitrate (Cu(NO3)2) was dissolved in 300 g of deionized water to obtain a solution, the solution was added to the impregnation bottle of the carrier, and after impregnation, the excess water was evaporated. The wet material was dried at 80°C for 8-10 hours, and then calcined at 500°C for 4 hours to obtain catalyst 3.

[0058] Example 4

[0059] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0060] Preparation of carrier: same as in Example 1.

[0061] Preparation of catalyst:

[0062] Weigh 429 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. Add 69.29 g of ammonium heptamolybdate ((NH4)6Mo7O 24 ·4H2O), 22.95 g ammonium metavanadate (NH4VO3), 47.59 g bismuth nitrate, 50.11 g ammonium metatungstate ((NH4)6H2W 12 O 40 ·nH2O), 4.35 g of copper nitrate (Cu(NO3)2) was dissolved in 300 g of deionized water to obtain a solution, the solution was added to the impregnation bottle of the carrier, after impregnation evenly, the excess water was evaporated. The wet material was dried at 80°C for 8-10 hours, and then calcined at 500°C for 4 hours to obtain catalyst 4.

[0063] Example 5

[0064] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0065] Preparation of carrier: same as in Example 1.

[0066] Preparation of catalyst:

[0067] Weigh 439 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. Add 51.97 g of ammonium heptamolybdate ((NH4)6Mo7O 24 ·4H2O), 22.95 g ammonium metavanadate (NH4VO3), 47.59 g bismuth nitrate, 50.11 g ammonium metatungstate ((NH4)6H2W 12 O 40·nH2O), 4.35g of copper nitrate (Cu(NO3)2) was dissolved in 300g of deionized water to obtain a solution, and the solution was added to the impregnation bottle of the carrier. After impregnation, the excess water was evaporated. The wet material was dried at 80°C for 8-10 hours, and then calcined at 500°C for 4 hours to obtain catalyst 5.

[0068] Example 6

[0069] This example provides an acrylic acid catalyst based on a spinel structure carrier, and the preparation method thereof comprises the following steps:

[0070] Preparation of carrier: same as in Example 1.

[0071] Preparation of catalyst:

[0072] Weigh 439 g of carrier 1 and place it in a rotary distillation impregnation bottle and evacuate for 1 hour. Add 34.64 g of ammonium heptamolybdate ((NH4)6Mo7O 24 ·4H2O), 22.95g ammonium metavanadate (NH4VO3), 47.59g bismuth nitrate, 50.11g ammonium metatungstate ((NH4)6H2W 12 O 40 ·nH2O), 4.35g copper nitrate (Cu(NO3)2) was dissolved in 300g deionized water to obtain a solution, the solution was added to the impregnation bottle of the carrier, after impregnation evenly, the excess water was evaporated. The wet material was dried at 80°C for 8-10 hours, and then calcined at 500°C for 4 hours to obtain catalyst 6.

[0073] Comparative Example 1:

[0074] 131g (NH4)6Mo7O 24 ·4H2O is added to a beaker, and then 400ml of deionized water is added. The temperature is slowly raised to 80℃ in a water bath, and stirred to dissolve to obtain solution A. Weigh 28.8g of ammonium metavanadate and 50.11g of ammonium metatungstate, mix them, and then add them to solution A. After they are completely dissolved, add ammonia water to adjust the pH to 6.0. Stir and react in a water bath at 80℃ for 30 minutes to obtain solution B. Add 83g of β-cyclodextrin to 5ml of warm water at 80℃, and stir to dissolve it as much as possible. Slowly add the obtained emulsion to solution B, stir and react for 20 minutes to obtain solution C. Weigh 0.15g of copper nitrate and add it to solution C. Stir and react in a water bath at 80℃ for half an hour to obtain solution D. Stop stirring and water bath heating, and then add 295g of mesoporous silica (40-60 mesh) into the cooled solution D, immerse for 5 minutes under mechanical stirring, then naturally air dry for 12 hours, dry at 120°C for 12 hours, and calcine at 500°C for 4 hours to obtain Comparative Example 1, with a catalyst strength of 36N / cm.

[0075] Test Case

[0076] In this example, the catalytic performance of the catalysts obtained in the above examples and comparative examples was investigated, and the evaluation conditions were:

[0077] Reactor: Fixed bed reactor, inner diameter 25.4 mm, reactor length 750 mm;

[0078] Catalyst filling amount: 150 g;

[0079] Reaction temperature: 260°C;

[0080] Response time: 2000h -1 ;

[0081] Raw material volume ratio: acrolein: air: water vapor = 1:3:2;

[0082] Raw material volume space velocity: 1200h -1 ;

[0083] The reaction product was absorbed by 0°C dilute acid and analyzed by gas chromatography. The carbon balance was calculated and the data were valid when the carbon balance was between 95% and 105%.

[0084] The component contents of the catalysts obtained in the above-mentioned embodiments and comparative examples are shown in Table 1, and the catalyst test results are shown in Table 2.

[0085] Table 1

[0086] project Mo, % V,% Bi, % W,% Cu, % Catalyst 1 12.0 3.5 / 2.0 0.2 Catalyst 2 12.0 3.5 3.5 2.0 0.2 Catalyst 3 10.0 2.0 2.0 2.0 0.2 Catalyst 4 8.0 2.0 2.0 2.0 0.2 Catalyst 5 6.0 2.0 2.0 2.0 0.2 Catalyst 6 4.0 2.0 2.0 2.0 0.2 Comparative Example 1 12.0 3.5 / 2.0 0.2

[0087] Table 2

[0088] catalyst Acrylic acid selectivity, % Acrolein conversion rate, % Acrylic acid yield, % Catalyst 1 83.3 92.6 87.1 Catalyst 2 89.4 96.3 88.2 Catalyst 3 90.2 98.5 88.6 Catalyst 4 90.6 99.1 90.1 Catalyst 5 85.5 95.3 86.4 Catalyst 6 80.1 87.2 77.3 Comparative Example 1 82.4 90.15 86.2

[0089] As shown in Table 2, the catalyst 4 obtained in Example 4 has the best catalytic performance, and the acrylic acid selectivity, acrolein conversion rate and acrylic acid yield can reach 90.6%, 99.1% and 90.1% respectively.

[0090] Based on the preparation process parameters of Example 4 and the above-mentioned test method, the key condition parameters are adjusted to illustrate the influence on the performance of the obtained catalyst.

[0091] Compared with Example 4, the key condition parameters were adjusted using the single variable method as shown in Tables 3, 4 and 5, and the performance test of the obtained catalyst was shown in Table 6.

[0092] Table 3

[0093] Adjust key parameters Example 4 Comparative Example 2 Comparative Example 3 Mo content 8.0% 12.0% 4.0%

[0094] Table 4

[0095] Adjust key parameters Example 4 Comparative Example 4 Comparative Example 5 Bi content 2.0% 3.5% 0%

[0096] Table 5

[0097] Adjust key parameters Example 4 Comparative Example 6 Comparative Example 7 V content 2.0% 3.5% 0%

[0098] Table 6

[0099] catalyst Acrylic acid selectivity, % Acrolein conversion rate, % Acrylic acid yield, % Comparative Example 2 89.8 97.1 87.2 Comparative Example 3 88.2 86.7 76.5 Comparative Example 4 90.3 94.8 85.6 Comparative Example 5 94.7 89.15 84.4 Comparative Example 6 90.1 93.4 84.2 Comparative Example 7 96.1 92.2 88.6

[0100] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0101] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing an acrylic acid catalyst based on a spinel structure carrier, characterized in that: The preparation method comprises the following steps: Pseudo-boehmite, magnesium nitrate and activated carbon powder are mixed, and then vaseline is added and mixed continuously to obtain a first mixture; adding ammonium fluoride and water to the first mixed material and mixing them to obtain a second mixed material; The second mixed material is extruded and pelletized, and then first dried and first calcined to obtain an Al2O3 carrier having a magnesium-aluminum spinel structure; The Al2O3 carrier is impregnated in a solution containing metal active components, and then subjected to a second drying and a second calcination to obtain the acrylic acid catalyst.

2. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The weight ratio of the pseudo-boehmite, the magnesium nitrate, the activated carbon powder, the vaseline, the ammonium fluoride and the water is (50-80):(0-5):(0-1):(0-1):(0-1):(20-36).

3. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The working condition parameters of the first drying include: drying at a temperature of 95 to 110° C. for 10 to 14 hours; the working condition parameters of the first calcining include: calcining at a temperature of 950 to 1250° C. for 3 to 5 hours.

4. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The physical and chemical properties of the Al2O3 carrier with a magnesium-aluminum spinel structure include: a specific surface area of ​​10 to 40 m 2 / g, strength 110~150N / cm.

5. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The metal active component includes at least one of a molybdenum source, a vanadium source, a bismuth source, a copper source and a tungsten source; the molybdenum source includes ammonium heptamolybdate, the vanadium source includes ammonium metavanadate, the bismuth source includes bismuth nitrate, the copper source includes copper nitrate, and the tungsten source includes ammonium metatungstate.

6. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The weight ratio of the Al2O3 carrier to the solution containing the metal active component is (0.1-1):(0.5-1.35).

7. The method for preparing an acrylic acid catalyst based on a spinel structure carrier according to claim 1, characterized in that: The working condition parameters of the second drying include: drying at a temperature of 70 to 90° C. for 8 to 10 hours; the working condition parameters of the second calcining include: calcining at a temperature of 400 to 600° C. for 3 to 5 hours.

8. An acrylic acid catalyst based on a spinel structure carrier, characterized in that: The acrylic acid catalyst based on a spinel structure carrier is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the acrylic acid catalyst based on a spinel structure carrier according to claim 8 in the preparation of acrylic acid using acrolein as a raw material.

Citation Information

Patent Citations

  • Composite metal oxide material

    CN1146439A

  • Compound catalyst for many metals oxide and preparation method

    CN1169619C

  • Composite metal oxide for unsaturated aldehyde selective oxidation and preparing method thereof

    CN1583261A

Cited By

  • Composite catalyst for preparing acrylic acid through selective oxidation of propylene and preparation method of composite catalyst

    CN121513892A